Evaluation of fingermillet (Eleusine coracana L.) genotypes for growth, yield and yield attributing traits in Vindhya region of Uttar Pradesh - Konigapaga Sindhuja; Prashant Kumar Rai; Vaidurya Pratap Sahi (Annals of Agricultural Research, 2025)
The field experiment entitled Evaluation of Finger millet ((Eleusine coracana L.) genotypes for growth, yield and yield Attributing traits in Vindhya region of Uttar Pradesh was conducted during kharif 2023 at field experimentation center, Departement of genetics and plant Breeding. SHUATS, Prayagraj, (U.P). The experiment was laid out in Randomized Block Desgin with eleven genotypes which were replicated thrice. The genotypes are as follows, IE-177, IE-183, IE-184, IE-185, IE-186, IE-196, IE-189, IE-203, FIN-7669 respectively. From the present study , it is concluded that among the 11 genotypes of Finger Millet, IE - 184 (14.30 gms ), followed by IE - 185 (14.23 gms), IE - 184 (29.51 gms), and IE - 185 (29.40 gms), recorded the highest seed yield per plant, seed yield per hectare. High GCV and PCV were recorded for the traits, Test weight, Seed yield per plant, Seed yield per plot, seed yield per hectare, plant height at 30 DAS. High heritability, coupled with genetic advance as a percent of the mean, was observed for the Test weight, Seed yield per plant, seed yield per plot, seed yield per hectare, plant height at 30 DAS. These genotypes are recommended for hybridization programs using will further improve crop performance and increase Finger Millet yield in the Vindhya region of Uttar Pradesh.